Uterine dynamics of the southern eagle ray Myliobatis goodei (Chondrichthyes: Myliobatidae) from the southwest Atlantic Ocean - Colonello, Jorge Horacio (2013)
Uterine layer changes and their relationship with the reproductive cycle were analyzed for the southern eagle ray Myliobatis goodei (Chondrichthyes: Myliobatidae), based on histological and histometric studies. The specimens were collected from bottom-trawl surveys conducted in the coastal southwest Atlantic ecosystem between latitude 34 and 42◦S. Oviduct samples were removed and fixed in 10% buffered formalin until processing for histological analysis. Both oviducts are developed in mature females, but only the left is functional. After ovulation, the size of the right posterior oviduct decreases and the left develops into a complex uterus that occupies almost the entire coelomic cavity. This uterus undergoes successive morphological and functional changes related to reproductive stages. Mucosa was characterized by temporal villous extensions or trophonemata with high variability depending on reproductive events. Invaginations or crypts associated with presumably lipid secretion (histotrophe) were observed between the trophonematum bases. The muscular layer develops into a complex muscular-vascular-conjunctive structure. The nutrition of early-gestation embryos is lecithotrophic and later they receive nutrients from the yolk sac and histotrophe. After yolk depletion, embryos become entirely dependent on histotrophe. Uterolactation, presumptive water imbibition of the muscular layer, and uterine hypertrophy observed in this study reinforce the “similarities” between Myliobatiformes and mammals.